2013
DOI: 10.12988/ams.2013.13015
|View full text |Cite
|
Sign up to set email alerts
|

MHD flow and heat transfer over an exponentially stretching sheet with viscous dissipation and radiation effects

Abstract: The steady two-dimensional laminar flow of a viscous incompressible electrically conducting fluid over an exponentially stretching sheet in the presence of a uniform transverse magnetic field with viscous dissipation and radiative heat flux is studied. By suitable similarity transformations, the governing boundary layer equations are transformed to ordinary differential equations and solved numerically by standard techniques. The effects of various parameters like, Magnetic and Radiation parameters, Prandtl nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…Also, increase of E + from 0 to 1e-4 increased the Nusselt number, but also decrease of Efrom 0 to -1e-4 decreased the Nusselt number. Variation of Nusselt number and so heat transfer was determined in [2,[9][10][11] as heat transfer in channels can be enhanced up to about 75% due to the presence of magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increase of E + from 0 to 1e-4 increased the Nusselt number, but also decrease of Efrom 0 to -1e-4 decreased the Nusselt number. Variation of Nusselt number and so heat transfer was determined in [2,[9][10][11] as heat transfer in channels can be enhanced up to about 75% due to the presence of magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Mansour et al [9] studied the effects of magnetic force, acting vertically downward on natural convection within a nanofluid filled tilted trapezoidal enclosure saturated with an electrically conducting fluid. As a result, Hartmann number increases the temperature gradients increases, hence heat transfer rate increases Jat and Chand [10] studied the steady 2-D laminar flow of a viscous incompressible electrically conducting fluid. Results showed that the shear stress decreases and heat transfer rate increases as magnetic parameter increases.…”
Section: Introductionmentioning
confidence: 99%
“…The flow of a viscous incompressible fluid over a stretching sheet has many interests over 10 years and was firstly considered by Sakiadis [1]. After many authors were focused this problem with extended conditions/situations like: two dimensional flow over a stretching sheet problem [2],heat transfer in the flow over stretching surface [3], boundary layer problem over an exponentially stretching sheet with thermal radiation [4], magneto hydrodynamic (MHD) boundary layer flow of a viscous fluid over an exponentially stretching sheet with radiation effect [5], MHD flow and heat transfer over an exponentially stretching sheet with viscous dissipation and radiation effects [6],etc.…”
Section: Introductionmentioning
confidence: 99%
“…DTM and Padé approximant was used to solve MHD flow problems in [8][9][10][11]. In this study the same problem with [6] which was solved numerically with Runge-Kutta method is considered and solved analytically with Differential Transform (DTM)-Padé method. The validity of the proposed approach has been confirmed by comparing the results [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A steady two-dimensional boundary layer flow of a viscous incompressible radiating fluid over an exponentially stretching sheet, in the presence of transverse magnetic field, is studied by Reddy and Reddy [13]. Recently, many researchers (e.g., Jat and Gopi Chand [14] and Wong et al [15]) studied the steady two-dimensional laminar flow of a viscous incompressible fluid over an exponentially stretching/shrinking permeable sheet with viscous dissipation and radioactive heat flux.…”
Section: Introductionmentioning
confidence: 99%